Lower Plasma β-Amyloid 1-42 Levels in Amnestic Mild Cognitive Impairment Compared to Healthy Individuals - Cynthia Cynthia; Jusak Nugraha; Muhammad Hamdan; Hari Basuki Notobroto; Silvia Francina Lumempouw; Rahajuningsih Dharma (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Amnestic mild cognitive impairment (aMCI) is strongly associated with an increased risk of progression to Alzheimer’s disease (AD). In AD, cerebrospinal fluid (CSF) β-Amyloid 1-42 levels are known to decrease, a pattern which is also observed in aMCI. While in AD, apolipoprotein E (ApoE) ε4 allele is known to be a genetic risk factor, the role of ApoE ε4 allele in modulating plasma β-Amyloid 1-42 levels in aMCI remains unclear. Therefore, this study was performed to evaluate plasma β-Amyloid 1-42 levels in aMCI patients compared to cognitively healthy individuals and investigate its association with ApoE ε4 allele.METHODS: A cross-sectional study involving 57 aMCI and 54 cognitively healthy control (HC) subjects was performed. Blood samples were taken from subjects from both groups for measurement of the plasma β-Amyloid 1-42 and ApoE ε4 allele. The plasma levels of β-Amyloid 1-42 were measured using an enzyme-linked immunosorbent assay (ELISA) methods, while the ApoE ε4 allele genotyping was conducted using polymerase chain reaction (PCR) techniques.RESULTS: Plasma β-Amyloid 1-42 in individuals with aMCI (23.9 pg/mL) was significantly lower than that in HC (25.3 pg/mL) with cut-off value of 24.6 pg/mL (AUC: 70.8%; 95% CI: 61.1–80.5%; p<0.001) sensitivity of 64.8%, and specificity of 71.9%. There was no significant association between plasma β-Amyloid 1-42 and the ApoE ε4 allele. However, plasma β-Amyloid 1-42 in ε4 carriers were lower than in ε4 non-carriers.CONCLUSION: Lower plasma β-Amyloid 1-42 levels were observed in aMCI patients compared to cognitively healthy individuals, suggesting its potential as a biomarker for identifying aMCI.KEYWORDS: blood biomarkers, amyloid beta peptides, amnestic mild cognitive impairment (aMCI)